REPRESENTATION TYPE OF DYNKIN QUIVER AND LOOP - ULA SAYYIDATUNNISA (NIM: 20115005), NURUL
Quiver or directed graph can be used to represent algebras and modules. There are two types of quiver's representation, that are finite type and in finite type. Those two types can be determined from the number of its indecomposable representation. In this thesis, we will investigate the representation type of loop quiver and Dynkin quiver referred to Gabriel's Theorem, by looking at pattern of inde- composable representation in An and Dn quiver, and also give a list of in- decomposable representation in E6;E7 and E8 quiver in form of graph of its dimension vectors.